Business Strategy of New Culinary Business in Balikpapan: A Case Study of Kedai Kadeen Restaurant - Sandi Augusta, Radar; Larso, Dwi (The Indonesian Journal of Business Administration, 2016)
Abstract. The culinary industry in Indonesia is one of the largest attractions towards the tourism sector in which it has contributed to 32.5% of GDP or close to 209 trillion Rupiahs. Kedai Kadeen is one of the many businesses that are present in Balikpapan’s culinary scene to delight local citizens and tourists alike with their region’s appetizing specialty dishes. However, as a newcomer in the city’s culinary sector, Kedai Kadeen faces several challenges to its establishment. Intense competition, low brand awareness, inconvenient business place, low service quality and unstable costs of raw materials, are the current business issues. A business research is conducted to address the problems that are currently being faced by Kedai Kadeen.  A quantitative method approach and literature review is used to explore probable solutions to the business issue. From the internal scanning using the 4P analysis, it was found that the business’s main strengths are in its location, products and promotional activities. The positioning for Kedai Kadeen is also in the right track as seen using STP analysis. Meanwhile, the main weaknesses of the restaurant are the limited space of business and facilities in the restaurant. The lack of employee control system, as seen using the Value Chain analysis, proved to be another liability towards the business process. Scanning of the external environment resulted in the discovery of several threats that can potentially slow down the business, especially threats from competitors as have been analyzed in the competitor analysis. However, using PEST and Porter’s Five Forces, it was found that there are still ample opportunities for growth in Balikpapan because of the market. Result of the analysis and SWOT mentioned above shows that Kedai Kadeen has only been able to obtain low level of revenue due to its non-optimal business strategy and lack of control systems. Thus the needs for strategic solution are required in order for Kedai Kadeen to grow and generate more revenue. Several business solution alternatives are proposed to overcome the business issues: Porter’s cost-leadership competitive and a 7P marketing mix. An implementation plan of these strategies and the needed resources are described. Key words: culinary management; entrepreneurship; business strategy; Balikpapan.